Analysis, Simulation, and Measurement of Micro-Vibrations in Reaction Wheels for High-Performance Imaging Missions - Du Plessis, Maria Richardt (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.